RPE association with lactate and heart rate during high-intensity interval cycling - Green, J. M.; McLester, J. R.; Crews, T. R.; Wickwire, P. J.; Pritchett, R. C.; Lomax, R. G. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Physiological and perceptual measures during interval exercise are not well understood. The current study therefore examined the correspondence between RPE, HR, and blood lactate concentration ([La]) during interval cycling.